Bandwidth Enhancement for Wireless Power Transfer System Employing Non-Linear Resonator - Xu Yang; Chaoqun Jiao; Junfeng Yang; Jing Fan; Dingzhen Li; Bao Wang (IEEE Access, 2021)
In order to enhance the tolerance of frequency misalignment and solve the amplitude-bandwidth limitation issue of the traditional linear resonance wireless power transfer (WPT) system, this paper proposes a non-linear resonance WPT (NLR-WPT) system which is mainly composed of high frequency power supply, primary linear resonator, secondary non-linear resonator, and load. Such non-linear resonator can be implemented with passive linear capacitor and magnetic saturation inductor, and it can be described by Duffing equation. It has been shown that the bandwidth of NLR-WPT system in the nonlinear state is 1.7 times larger than that in the linear state. In addition, the output voltage basically stabilizes at the same level, the voltage fluctuation is less than 5% over the power frequency ranging from 25.6 kHz to 31.8 kHz, and high overall efficiency of 86.5% can be achieved under a wide range of frequency (27.5 kHz-30.1 kHz). Furthermore, the range of frequency can be extended significantly over which the output voltage is maintained even while the compensate capacitance, load, or coupling coefficient values vary in a certain range. The experimental results agree well with the theoretical analysis and verify the validity of the NLR-WPT system with non-linear resonator. This paper provides a simple and effective scheme to suppress the fluctuation of output voltage, which is suitable for the applications of constant voltage charging such as moving devices or electric vehicles.